Assessment of middle school teachers’ curriculum awareness and instructional planning practices: A mixed-methods study - Aygün, Coşkun; Kuloğlu, Ayşenur (Eğitim Programları ve Öğretim Derneği, 2026)
This study aims to assess middle school teachers' awareness of curriculum and instructional planning practices. The research was conducted during the 2021-2022 academic year in Elazığ, covering 50 middle schools. In the quantitative phase, data were collected from 239 teachers through convenience sampling, whereas the qualitative phase included 41 teachers, selected using maximum variation sampling to ensure diverse representation. A mixed-methods approach was adopted, integrating both quantitative and qualitative research designs. The quantitative dimension employed a descriptive survey model to gather teachers' perspectives, while the qualitative dimension utilized a case study design to analyze their in-depth experiences. Quantitative data were collected using the "Curriculum Awareness Scale," while qualitative data were obtained through semi-structured interviews. The qualitative data analysis was conducted using content analysis, where emerging themes and patterns were identified. To ensure data reliability, expert validation and structured coding techniques were implemented. The findings indicate that teachers' levels of curriculum awareness vary, influenced by factors such as individual experience, professional development, and institutional settings. Additionally, the qualitative results emphasize the role of collaborative planning in enhancing instructional effectiveness. The study suggests that while teachers generally have a good understanding of the curriculum, some challenges arise during practical implementation. Addressing these challenges through targeted professional development programs and structured instructional planning strategies could enhance curriculum awareness. The results highlight the significance of integrating both quantitative and qualitative methods to gain a comprehensive understanding of teachers' instructional practices.
Keywords: Curriculum awareness; Instructional planning; Middle school teachers; Mixed-methods research